Addressing Pressing Needs in the Development of Advanced Therapies - Morrow, David; Ussi, Anton; Migliaccio, Giovanni (Frontiers in Bioengineering and Biotechnology, 2017)
The commercial development of Advanced Therapy Medicinal Products (ATMPs) represents great opportunity for therapeutic innovation, but is beset by many challenges for its developers. Although the ATMP field continues to progress at a rapid pace, evidenced by the increasing number of clinical trials conducted over the last few years, several factors continue to complicate the introduction of ATMPs as a curative treatment for multiple disease types, by blocking their translational pathway from research to the patient. While several recent publications (1-3) as well as an Innovative Medicines Initiative (IMI) consultation (4) this year have highlighted the major gaps in ATMP development, with manufacturing, regulatory and reimbursement issues at the forefront, there remains to be formulated a coherent strategy to address these by bringing the relevant stakeholders to a single forum, whose task it would be to design and execute a delta plan to alleviate the most pressing bottlenecks. This white paper focuses on two of the most urgent areas in need of attention in ATMP development, namely manufacturing and reimbursement, and promotes the concept of innovation-dedicated research infrastructures to support a multi-sector approach for ensuring the successful development, entry and ensuing survival of ATMPs in the healthcare market.